THE YOUTH UNEMPLOYMENT IN SRAGEN REGENCY: SAKERNAS DATA ANALYSIS - Muhit Nur Hidayah (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
The existence of a long-term demographic transition has an impact on the young population explosion,  even the population trend shows a growing pattern of the young population. It is unfortunate if the number of young age people who are not absorbed in employment will eventually become unemployed. Unemployment at a young age will have an impact on the amount of unemployment. This study will analyze the demographic factors and human capital that underlie youth unemployment in Sragen in 2021. The research employs the raw data derived from the results of the National Labor Force Survey (SAKERNAS) in Agustus 2021 from the Statistics Indonesia (BPS) of Sragen Regency. The method used is binary logistic regression analysis. The results showed that the variables of age, gender, the status of a household, marital status, training, middle school education, and high school education affect the tendency of the young workforce to become unemployed.